Cuscutae Semen in depression-induced ovarian dysfunction: metabolomics with UPLC-QToF-MS in female mice - Xie, Ying; Zeng, Zhaoxiang; Zhang, Jinrong; Han, Qiangqiang; Song, Chengwu; Jin, Shuna; Zhao, Min (Frontiers in Molecular Biosciences, 2025)
The increasing prevalence of depression profoundly affects female ovarian health. Although Cuscutae Semen (CS) is acknowledged for treating reproductive disorders, its pharmacological mechanisms in depression-induced ovarian dysfunction remain insufficiently explored. This study investigated CS’s effects in a chronic unpredictable mild stress (CUMS) mouse model of depression. Mice were divided into control, CUMS model, CS treatment and estradiol treatment group. Behavioral and biochemical analyses assessed depressive-like behaviors and hormone levels. Untargeted metabolomics utilizing ultra-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry was applied to identify differential metabolites of CS in the treatment of depression-induced ovarian dysfunction. These findings were confirmed through real-time quantitative polymerase chain reaction assays. Based on the outcomes from behavioral and biochemical assays, CS effectively ameliorated the chronic unpredictable mild stress-induced reproductive ailment in mice. Ten differential metabolites were identified, highlighting the impact of CUMS and CS’s ameliorative effects. Pathways linked to arachidonic acid metabolism, glycerophospholipid metabolism, linoleic acid metabolism, and steroid hormone biosynthesis were involved. Seven target genes further validated the metabolomic analysis. This study provides strong evidence of CS’s therapeutic potential in alleviating depression-induced ovarian dysfunction, shedding light on its pharmacological mechanisms and supporting its use as a functional medical food.